Islamic Bank Productivity: Analysis of Research Path - Fatimah Iskandar Putri (SMART Insight, 2022)
This study aims to see the development of research Islamic Bank Productivity around the world published by journals with that theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme Islamic Bank Productivity derived from the Scopus database for 2005-2022. Then, the data was processed and analyzed using the VosViewer application with the aim of knowing the research development bibliometric map Islamic Bank Productivity in this world. The results of the study found that the authors, organizations, and countries with the most publications were dominated by Malaysia. Next, Islamic Bank Productivity based on the bibliometric keyword mapping, there are 4 clusters which are research lines in the existing literature, namely the determinants of Islamic bank productivity, the effect of capital on Islamic bank productivity, the effect of macroeconomic variables on Islamic bank productivity, and the effect of interest rates on Islamic bank productivity.